COVID-19 Surgical Abortion Restriction Did Not Reduce Visits to Abortion Clinics - Martin Andersen; Sylvia Bryan; David Slusky (Institute of Labor Economics (IZA), 2020)
Due to COVID-19, 33 states banned elective medical procedures, and 13 of these states included surgical abortions. We collected street addresses of abortion clinics and linked them to SafeGraph's data on counts of visitors. We found a 32 percent decrease in clinics visits in February-May of 2020 compared to 2019. States that banned elective procedures saw an additional 23 percent decrease in visits. However, there was no significant additional decrease in the states that explicitly banned surgical abortions. We estimate that the decrease in foot traffic over these four months reduced abortions by 9 percent in 2020 relative to 2019.
Keywords: H75; I18; J13; 330; COVID-19; elective surgery; social distancing; abortion